2008
DOI: 10.1111/j.1540-8167.2008.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Atrial Fibrillation in Patients with Diabetes Mellitus Type 2: Results from a Randomized Study Comparing Pulmonary Vein Isolation Versus Antiarrhythmic Drug Therapy

Abstract: In patients with DM2, CA of AF provides significant clinical benefits over the ADT and appears to be a reasonable approach regarding feasibility, effectiveness, and low procedural risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 28 publications
6
90
0
4
Order By: Relevance
“…Mniej jest dostępnych danych na temat skuteczności i bezpieczeństwa ablacji przezcewnikowej u pacjentów z przetrwałym lub długotrwale przetrwałym AF, ale wszystkie one wskazują na mniejszą częstość nawrotów po ablacji przezcewnikowej w porównaniu z farmakoterapią antyarytmiczną, połączoną lub niepołączoną z kardiowersją (dodatkowa ryc. 2) [185,717,[723][724][725][726]1039]. U pacjentów doświadczających objawowych nawrotów AF mimo farmakoterapii antyarytmicznej we wszystkich RCT wykazano lepsze utrzymywanie rytmu zatokowego po ablacji przezcewnikowej niż podczas stosowania leków antyarytmicznych [586,713,727,728].…”
Section: Wskazaniaunclassified
See 1 more Smart Citation
“…Mniej jest dostępnych danych na temat skuteczności i bezpieczeństwa ablacji przezcewnikowej u pacjentów z przetrwałym lub długotrwale przetrwałym AF, ale wszystkie one wskazują na mniejszą częstość nawrotów po ablacji przezcewnikowej w porównaniu z farmakoterapią antyarytmiczną, połączoną lub niepołączoną z kardiowersją (dodatkowa ryc. 2) [185,717,[723][724][725][726]1039]. U pacjentów doświadczających objawowych nawrotów AF mimo farmakoterapii antyarytmicznej we wszystkich RCT wykazano lepsze utrzymywanie rytmu zatokowego po ablacji przezcewnikowej niż podczas stosowania leków antyarytmicznych [586,713,727,728].…”
Section: Wskazaniaunclassified
“…W celu uzyskania kontroli objawów większość pacjentów wymaga więcej niż jednego zabiegu [713,726,728]. Zasadniczo rzecz biorąc, lepszych wyników leczenia pod względem utrzymywania rytmu zatokowego oraz mniejszej częstości występowania powikłań związanych z zabiegiem można oczekiwać u młodszych pacjentów z krótkimi wywiadami AF oraz często występującymi, krótkotrwałymi epizodami AF przy braku istotnej strukturalnej choroby serca [745].…”
Section: Wyniki Ablacji Przezcewnikowej Migotania Przedsionkówunclassified
“…Catheter ablation of AF provides a possibility to maintain sinus rhythm without the use of AADs in the large proportion of selected patients with AF, and it represents a promising alternative to available pharmacological therapy for rhythm control. Table 2 presents several randomized studies which compared efficiency and safety of AADs versus catheter ablation for the treatment of patients with AF [90][91][92][93][94][95][96][97][98][99]. Clinical follow-up in these studies most often was 1 year, whilst only one study reported long term results.…”
Section: Figure 3 Catheter Ablation Of Persistent Af: Pv Isolation Amentioning
confidence: 99%
“…propafenone, flecainide and disopyramide) or class III AAD (i.e. sotalol, amiodarone and dofetilide) [91][92][93][94][95][96][97]99]. In addition, two studies compared the results of transcatheter and pharmacological therapy as the first therapeutic option in patients with previously untreated AF [90,98].…”
Section: Figure 3 Catheter Ablation Of Persistent Af: Pv Isolation Amentioning
confidence: 99%
“…However, the management recommendations and guidelines have not yet reached a consensus with regard to the use of catheter ablation for the treatment of AF, primarily due to the differences in ablation strategy and technique employed in different centers, in addition to relevant complications (5,6,8). In previous years, a number of small to moderately sized randomized controlled trials (RCTs) have been published that directly compare the efficacy of catheter ablation and AADs for the treatment of AF (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). However, the number of patients enrolled in each study was limited.…”
Section: Introductionmentioning
confidence: 99%